Adlay (Coix lachryma-jobi L. var. ma-yuen Stapf.) Hull Extract and Active Compounds Inhibit Proliferation of Primary Human Leiomyoma Cells and Protect against Sexual Hormone-Induced Mice Smooth Muscle Hyperproliferation - Lin, Po-Han; Shih, Chun-Kuang; Yen, Yu-Ting; Chiang, Wenchang; Hsia, Shih-Min (Molecules (Basel, Switzerland), 2019)
Uterine leiomyomas, also known as fibroids, are benign neoplasms of the uterus and have a high incidence rate in women of reproductive age. Hysterectomy or myomectomy is the initial treatment, but fibroids will recur if the patient is still exposed to similar risk factors. Therefore, developing new therapeutic strategies are urgently necessary. In this study, the anti-proliferation effects of each fraction of adlay seeds were evaluated in uterine leiomyomas, and we identified the potential phytochemical compounds. We found that the ethyl acetate fraction of adlay hull (AHE-ea) appeared to be highly efficient in the anti-proliferation of rat uterine leiomyoma ELT3 cells and primary human uterine leiomyoma (hUL) cells. The proliferation of primary human normal uterine smooth muscle (UtSMC) and normal uterine myometrial (hUM) cells were also suppressed by AHE-ea. Two phytosterols, stigmasterol and β-sitosterol, were identified from AHE-ea fraction. Mice treated with AHE-ea and stigmasterol alone demonstrated reduced diethylstilbestrol/medroxyprogesterone 17-acetate (DES/MPA)-induced uterine myometrial hyperplasia, which is the critical step for the development of leiomyoma. Taken together, our results suggest that the AHE-ea fraction could be considered as a natural plant-based medicine in the prevention or treatment of uterine leiomyoma growth.